Age-dependent skill formation and returns to education: simulation based evidence - Friedhelm Pfeiffer; Karsten Reuß (Institute for the Study of Labor (IZA), 2007)
This study integrates findings from neurobiology and psychology on early childhood development and self-regulation to assess returns to education. Our framework for evaluating the distribution of age-specific returns to investments in cognitive and noncognitive skills is a lifecycle simulation model based on the technology of skill formation (Cunha and Heckman (2007)). Our findings illustrate the cumulative and synergetic nature of skill formation, the skill multiplier, and the shaping role early childhood has for human capital formation, growth and inequality.
Keywords: 330; Bildungsverhalten; Lebenszyklus; Bildungsinvestition; Bildungsertrag; Persönlichkeitspsychologie; Altersgruppe; Schätzung; Deutschland